Analysis of Delay Limitation and Circuit Power Balance Optimisation for CMOS Based Circuits - Li , Ruotong (Transactions on Computer Science and Intelligent Systems Research, 2024)
As integrated circuits and technology have advanced, people’s requirements for integrated circuits are getting higher and higher, and integrated circuits with high performance, low latency and low power consumption characteristics are needed to satisfy all kinds of human needs. However, meeting these needs requires a balanced optimization of circuit delay and energy consumption. The gate size and voltage need to be varied simultaneously, and the most suitable voltage and gate are found by combining the gate size and voltage ratio using a linear programming solver. This method can find the optimal gate size and voltage for minimum power circuits with delay requirements, and it also provides new possibilities for comprehensive optimization of Complementary Metal Oxide Semiconductor (CMOS) integrated circuits from both performance and energy perspectives and provides new ideas for IC optimization. In the future, it is necessary to continue to explore the automatic optimization techniques and use deep learning techniques to obtain more efficient circuit optimization methods.